2011
DOI: 10.3386/w17666
|View full text |Cite
|
Sign up to set email alerts
|

Do Borrower Rights Improve Borrower Outcomes? Evidence from the Foreclosure Process

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Policymakers should consider this finding when designing well-intentioned policies that lengthen the foreclosure timeline. As discussed by Gerardi, Lambie-Hanson, and Willen (2013), judicial foreclosure proceedings and state-specific right-to-cure periods lengthen the average foreclosure timeline but do not improve the probability that borrowers self-cure their mortgage defaults or receive mortgage modifications. Policies that lengthen the foreclosure process extend the time properties are in ownership limbo, which could result in more problems from deferred maintenance.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Policymakers should consider this finding when designing well-intentioned policies that lengthen the foreclosure timeline. As discussed by Gerardi, Lambie-Hanson, and Willen (2013), judicial foreclosure proceedings and state-specific right-to-cure periods lengthen the average foreclosure timeline but do not improve the probability that borrowers self-cure their mortgage defaults or receive mortgage modifications. Policies that lengthen the foreclosure process extend the time properties are in ownership limbo, which could result in more problems from deferred maintenance.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Mian et al (2011) argue that US states that slow down foreclosures have recently performed better than those that allow rapid foreclosures; Gerardi et al (2011) counter that slower foreclosures still take place eventually, generating the same or perhaps even greater external e¤ects as houses are occupied for longer periods of time by distressed owners.…”
Section: Mortgage Modi…cationmentioning
confidence: 99%
“…These studies identified a wide range of factors that affect mortgage outcomes, with state laws governing foreclosure, the amount of home equity, credit scores at origination, and presence of junior liens among the most significant (Voicu et al 2012b;Chan et al 2013;Gerardi et al 2013). Interventions, such as mortgage default counseling, were also shown to substantially increase the probability that a borrower receives a loan modification and reduce the probability of foreclosure ).…”
Section: Previous Literaturementioning
confidence: 99%